1982
DOI: 10.1073/pnas.79.10.3203
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet-derived growth factor stimulates amino acid transport and protein synthesis by human diploid fibroblasts in plasma-free media.

Abstract: Purified human platelet-derived growth factor (PDGF) induces an increase in amino acid uptake via system A in quiescent human diploid fibroblasts. Cells must be exposed to PDGF for 45 min to obtain maximum transport stimulation. Transport stimulation requires protein synthesis. Transient exposure to PDGF, alone, in the absence of plasma components can stimulate transport. Acid-insoluble [3H]leucine incorporation is also stimulated by PDGF treatment, and this event also does not require the presence of plasma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Additionally such ligand-receptor interaction induces pleiotropic effects in the cell including enhanced glycolysis, increased amino acid transport, calcium, sodium and hydrogen ion exchange and protein synthesis (Owen et al, 1982). Another growth factor, transforming growth factor alpha (TGFa) binds to the EGFR.…”
mentioning
confidence: 99%
“…Additionally such ligand-receptor interaction induces pleiotropic effects in the cell including enhanced glycolysis, increased amino acid transport, calcium, sodium and hydrogen ion exchange and protein synthesis (Owen et al, 1982). Another growth factor, transforming growth factor alpha (TGFa) binds to the EGFR.…”
mentioning
confidence: 99%
“…The time course and dose dependency were similar to those reported previously by others. 16 The amino acid uptake by PDGF-stimulated VSMCs reached a plateau at 4 hours, with maximum values of a 1.4-fold increase over controls for leucine, 1.7-fold for arginine, and 1.8-fold for proline ( Figure 1A). The uptake of all amino acids was stimulated with 1 to 5 ng/mL PDGF-BB, and higher concentrations did not further increase the uptake ( Figure 1B).…”
Section: Pdgf Stimulates Vsmc Uptake Of 3 Different Amino Acids Throumentioning
confidence: 99%
“…Besides growth, the cellular effects of PDGFs include chemotaxis (Grotendorst et al 1982;Siegbahn et al 1990), differentiation (Raff 1989;Richardson 1990), and modulation of other cell functions such as the production of extracellular matrix components (Owen et al 1982;Majack et al 1985) and contraction (Berk et al 1986;Gullberg et al 1990). Following its identification as a secretory product of platelets (Balk 1971;Busch et al 1976), PDGFs have been shown to be synthesized by numerous normal cell types, including endothelial cells, monocytes/macrophages, smooth muscle cells, fibroblasts, placenta cytotrophoblasts, neurons, and certain glial cells (for review, see Heldin and Westermark 1990;Raines et al 1990;Raines and Ross 1993).…”
mentioning
confidence: 99%